Pengaruh Motivasi Kerja, Pelatihan, Pengalaman Kerja dan Promosi Jabatan Terhadap Kinerja Guru SMP di Strada Cabang Tangerang - Anastasia Puji Lestari; Widi Dewi Ruspitasari; Murtianingsih Murtianingsih (Smart Education, 2024)
The teachers' performance is the result or achievement of work carried out by teachers based on the competence on their duties and responsibilities as teachers. Teachers' performance is important in an educational institution; it can influence the progress of the institution. Perkumpulan Strada is one of the educational institutions that has a vision and mission to create superior and character-building students. The purpose of this study is to determine whether work motivation, training, work experience, and job promotion affects the performance of junior high school teachers at Perkumpulan Strada Cabang Tangerang. The research used multiple linear regression method with the assistance of SPSS 29 software. The sampling method involved purposive sampling with 74 respondents. The study used online data collection by google form and hypothesis testing to validate the research. The results showed that work motivation and training do not significantly affect the performance of junior high school teachers in Perkumpulan Strada Cabang Tangerang, but work experience and job promotion do. Whereas, those variables can simultaneously affect the performance of junior high school teachers in Perkumpulan Strada Cabang Tangerang.Â Keyword: Work's Motivation, Training, Work's Experience, Promotion, Tecahers' Performance